Effect of Artificial Insemination on different production parameter in Hubbard classic broiler parent stock (Journal of the Bangladesh Agricultural University, 2016)
The experiment was conducted to determine the effect of artificial insemination (AI) on different production parameter in Hubbard Classic Broiler breeder parent stock. A total number of 300 female and 30 male Hubbard Classic broiler breeder parent stock birds were used as experimental animals and parameter recorded are: Health condition and body weight of birds, % of Production, % Hatchability,% Uniformity, grade A chicks, mortality % , hatching egg % & effect of diluents use, birth weight of day old chick (DOC). Significant variation (p